2020
DOI: 10.1080/21655979.2020.1834726
|View full text |Cite
|
Sign up to set email alerts
|

Systems pharmacology in combination with proteomics reveals underlying mechanisms of Xihuang pill against triple-negative breast cancer

Abstract: Xihuang pill (XHP), a traditional Chinese herbal formula, has been clinically used as an adjuvant therapy against triple-negative breast cancer (TNBC) via inhibiting cancer cell invasion and proliferation, as well as promoting cancer cell apoptosis. However, its anti-TNBC bio-active ingredients and possible mechanisms are still unclear. Herein, the hub bioactive compounds and underlying mechanisms of XHP against TNBC were systematically elucidated by integrating systems pharmacology approach and in vitro prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
(88 reference statements)
1
6
0
Order By: Relevance
“…The whole prescription is composed of calculus bovis, musk, frankincense, and myrrh. It is commonly applied in the prevention and treatment of breast cancer, cervical cancer, and other tumors ( Wu et al, 2020 ; Xu X et al, 2020 ), but its effect on prostate cancer and exact mechanism are unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The whole prescription is composed of calculus bovis, musk, frankincense, and myrrh. It is commonly applied in the prevention and treatment of breast cancer, cervical cancer, and other tumors ( Wu et al, 2020 ; Xu X et al, 2020 ), but its effect on prostate cancer and exact mechanism are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is recorded that it can be applied in malignant diseases such as Shi-ju, Ru-yan, and E-he. Nowaday, XHP have been used in the treatment of various cancers, such as breast cancer, lung cancer, lymphoma, and so on, and have achieved certain efficacy ( Fu et al, 2020 ; Li et al, 2020 ; Xu X et al, 2020 ). The antitumor mechanism of XHP is via inducing tumor cell apoptosis ( Su et al, 2018 ), inhibiting tumor cell proliferation ( Hao et al, 2018 ), blocking the cell cycle, and regulating tumor microenvironment ( Yang et al, 2020 ), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to previous studies [61][62][63], we conducted an analysis combining genomic data with drug database analysis to identify novel candidate therapeutic agents for breast cancer treatment. Our study demonstrates the usefulness of this approach for evaluating the relationship among genes, diseases, and drugs.…”
Section: Discussionmentioning
confidence: 99%
“…A systems pharmacology and proteomics study of XHW on triple-negative breast cancer (TNBC) showed that XHW may be effective on non-small cell lung cancer and small cell lung cancer, as demonstrated by the KEGG signaling pathway enrichment analysis (52).…”
Section: Discussionmentioning
confidence: 99%